The abuse of authority crime. Dogmatic and political-criminal considerations - Pariona Arana, Raúl (2015)
In a State governed by the rule of law and respect for institutions, the power is never absolute, but rather a limited one. In that order, when public officials exceed their authority and attributions, the legal system should have a reaction.In the present article, the author realizes an explanation and an analysis about the abuse of authority crime. According to national and international doctrine, and Peruvian jurisprudence, the author presents how to understand the legal right protected, the objective and subjective tipicity, the active and passive subjects, as well as the sanction in this crime.